MicroRNA-133b Negatively Regulates Zebrafish Single Mauthner-Cell Axon Regeneration through Targeting tppp3 in Vivo - Huang, Rongchen; Chen, Min; Yang, Leiqing; Wagle, Mahendra; Guo, Su; Hu, Bing (Frontiers in Molecular Neuroscience, 2017)
Axon regeneration, fundamental to nerve repair and functional recovery, relies on rapid changes in gene expression attributable to microRNA (miRNA) regulation. MiR-133b has been proved to play an important role in different organ regeneration in zebrafish, but its role in regulating axon regeneration in vivo is still controversial. Here, combining single-cell electroporation with a vector-based miRNA-expression system, we have modulated the expression of miR-133b in Mauthner-cells (M-cells) at the single-cell level in zebrafish. Through in vivo imaging, we show that overexpression of miR-133b inhibits axon regeneration, whereas down-regulation of miR-133b, promotes axon outgrowth. We further show that miR-133b regulates axon regeneration by directly targeting a novel regeneration-associated gene, tppp3, which belongs to Tubulin polymerization-promoting protein family. Gain or loss-of-function of tppp3 experiments indicated that tppp3 was a novel gene that could promote axon regeneration. In addition, we observed a reduction of mitochondrial motility, which have been identified to have a positive correlation with axon regeneration, in miR-133b overexpressed M-cells. Taken together, our work provides a novel way to study the role of miRNAs in individual cell and establishes a critical cell autonomous role of miR-133b in zebrafish M-cell axon regeneration. We propose that up-regulation of the newly founded regeneration-associated gene tppp3 may enhance axonal regeneration.